The Impact of Burnout Towards Organizational Citizenship Behavior (OCB) in Premier Surabaya Hospital - Fernaldi Kurniawan (iBuss Management, 2015)
This research is conducted to know the impact of Burnout towards Organizational Citizenship Behavior (OCB), especially in Premier Surabaya Hospital. In addition, it also wants to compare the Burnout level between group of departments dealing directly with customers and group of departments do not dealing directly with customers. Oldenberg Burnout Inventory consisting of two Burnout dimensions is used to measure the Burnout level. The two dimensions are Exhaustion and Disengagement. Organ’s OCB instruments is used in measuring the OCB level. Non-probability, purposive judgement sampling method is used in this research. Samples are taken from 15 chosen departments in Premier Surabaya Hospital. In the end, 101 samples can be used for the analysis.Multiple Linear Regression is used to analyze the impact of Burnout towards OCB. The result shows that Burnout has a significant negative effect towards OCB. The author also compare the Burnout level between group of departments dealing directly with customers and group of departments do not dealing directly with customers using Independent Sample t-Test. The result shows that there is no significant difference between the Burnout level of the two groups of departments. Keywords: Burnout, Organizational Citizenship Behavior, OCB, Healthcare, Premier Surabaya Hospital